ASAI KEMAMPUAN BAKTERI ENDOFIT DARI KACANG TANAH DALAM MENGHAMBAT PERTUMBUHAN Sclerotium sp. PADA KECAMBAH KACANG TANAH - Lisa Novita Arios; Dwi Suryanto .; Kiki Nurtjahja .; Erman Munir . (Universitas Lampung, 2014)
Assay on ability of endophytic bacteria isolated from peanut to inhibit Sclerotium sp. growth in peanut seedlings. A study on assay of ability of endophytic bacteria to inhibit Sclerotium sp. in peanut seedling has been done. The bacteria were isolated from peanut healthy plants, while Sclerotium sp. was isolated from infected peanaut plant. Antagonistic assay was conducted by dual culture method. In vivo assay of inhibiting Sclerotium sp. was conducted by dipping peanut seed in bacterial solution, and planting the seed in soil:compost (3:1) growing media. Six endophytic bacterial isolates showed to inhibit the growth of Sclerotium sp. in vitro. LN1 seemed to inhibit more of Sclerotium sp., while LN5 showed to inhibit less. Two potential isolates LN1 of gram-negative and LN2 of gram-positive using for further study showed to decrease more of dumping off. It also seemed that the isolates increased the seedling height, number of leaves, and dry weight.